THE INFLUENCE OF KEGEL EXERCISE ON ELDERLY PATIENTS WITH URINARY INCONTINENCE IN TECHNICAL IMPLEMENTATION UNIT OF SOCIAL SERVICE TRESNA WERDHA JOMBANG - Lexy Oktora Wilda; Nungki Dwi Andriani (Nurse and Health: Jurnal Keperawatan, 2018)
Background: Urinary incontinence is an uncontrolled release of urine in considerable amounts, this is due to changes in bladder structure and pelvic floor muscle resulting in the elderly being unable to withstand urine during urination.Objectives: The aims of this research were to determine the influence of kegel exercise on elderly patients with urinary incontinence in Technical Implementation Unit of Social Service Tresna Werdha Jombang.Method: The design of pre-experimental research design with one group pre-post-test design approach, conducted on 25 April to 25 May 2018. The Population of all elderly urinary incontinence in Technical Implementation Unit of Social Service Tresna Werdha Jombang were 10 respondents. Sampling technique total sampling. Independent variable of kegel exercise, dependent variable urinary incontinence. Data collection using ICIQ - UI SF questionnaire. Statistical test using Wilcoxon with significant level α = 0.05.Results: The Result of the study from 10 respondents, mostly 7 respondents (70%) before the kegel exercise had moderate urinary incontinence, while almost all of 8 respondents (80%) after kegel exercise had mild urinary incontinence. Wilcoxon statistical test result obtained p value = 0,008 ≤ 0,05 then Ha accepted so that there is influence of kegel exercise on elderly patients with urinary incontinence in Technical Implementation Unit of Social Service Tresna Werdha Jombang.Conclusion: Kegel exercise proved to increase pelvic floor muscle strength and reduce urinary incontinence, so it is necessary to do the elderly regularly and periodically. Key words: Kegel Exercise, Urinary Incontinence, Elderly.